National “Kurash”: History and Contemporary (On the Example of the Uzbek People) - Jalilov, Ikhtiyor (Procedia of Social Sciences and Humanities, 2021)
Just as every nation in the world has its own national sport, the history of Uzbek national kurash goes back a long way, and they have been improving over the centuries and are still respected as a national and universal value.